1998
DOI: 10.1038/sj.onc.1201860
|View full text |Cite
|
Sign up to set email alerts
|

A chicken c-Rel-estrogen receptor chimeric protein shows conditional nuclear localization, DNA binding, transformation and transcriptional activation

Abstract: In this report, we characterize the biological and biochemical properties of a conditional protein containing chicken c-Rel fused to the hormone-binding domain of the human estrogen receptor. This chimeric c-RelER protein causes estrogen-dependent, but otherwise c-Relspeci®c, transformation of avian ®broblasts in vitro. Our results demonstrate that c-RelER heterodimerizes with wild-type c-Rel and forms speci®c complexes with IkB-a. Estrogen causes translocation of c-RelER to the nucleus and stabilizes its bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…This suggests that v-Rel promotes toxicity by binding to DNA and a ecting gene expression (see below). Overexpression of chicken cRel can induce G 1 -S phase cell-cycle arrest in HeLa cells and CEF Zurovec et al, 1998), and this could also be the mechanism by which v-Rel is toxic. However, the cytotoxicity of v-Rel in mammalian cells has not been investigated in any comprehensive way, and it appears that at least one mammalian cell type, D17 dog osteosarcoma cells, can tolerate high-level expression of v-Rel (TD Gilmore, 1999 unpublished results).…”
Section: Malignant Transformation By C-rel Mutantsmentioning
confidence: 99%
“…This suggests that v-Rel promotes toxicity by binding to DNA and a ecting gene expression (see below). Overexpression of chicken cRel can induce G 1 -S phase cell-cycle arrest in HeLa cells and CEF Zurovec et al, 1998), and this could also be the mechanism by which v-Rel is toxic. However, the cytotoxicity of v-Rel in mammalian cells has not been investigated in any comprehensive way, and it appears that at least one mammalian cell type, D17 dog osteosarcoma cells, can tolerate high-level expression of v-Rel (TD Gilmore, 1999 unpublished results).…”
Section: Malignant Transformation By C-rel Mutantsmentioning
confidence: 99%
“…Together, these ®ndings are consistent with a model in which the loss of the C-terminal transactivation domain of c-Rel may provide a selective growth advantage. c-Rel and other NF-kB factors have been shown to induce growth arrest or display a pro-apoptotic phenotype when expressed at high levels in some systems (Abbadie et al, 1993;Bash et al, 1997;Grimm et al, 1996;Huguet et al, 1997;Seitz et al, 1998;Sheehy and Schlissel, 1999;Zurovec et al, 1998). These ®ndings suggest that structural alterations in c-rel may be necessary in some cases for the manifestation of its oncogenic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Fusion of the hormone-binding domain of the human estrogen receptor (ER) to v-Rel (Boehmelt et al, 1992;Capobianco and Gilmore, 1993), chicken c-Rel (Zurovec et al, 1998), and mouse c-Rel (Grumont et al, 1999) has been shown to confer estrogendependent transcriptional activation activity onto these proteins. Therefore, in an effort to create a conditional human c-Rel (REL) protein, we fused human ER sequences at the C terminus of a highly transforming mutant of REL, RELD424-490 ( Figure 1a).…”
mentioning
confidence: 99%
“…Whether the contrasting effects of estrogen on v-Rel-ER versus RELD424-490-ER are due to a mutation that has occurred in v-Rel (for example, a mutation that abolishes its ability to be regulated by estrogen-ER), are due to a natural sequence difference between v-Rel and human REL, or are due to a peculiarity of the fusion design is not clear. Of note, there is an aminoacid sequence in human REL (LTTAL, aa 163-167) that is similar to a consensus nuclear receptor interacting motif (LXXLL) that can be bound by ERa (Gee et al, 1999;Robyr et al, 2000); the corresponding sequence is different in v-Rel (YTLAL, aa 171-175), chicken c-Rel (YTLAL, aa 162-166), and mouse c-Rel (FTTAV, aa 163-167), all of which are regulated in the conventional fashion when expressed as ER fusion proteins (Capobianco and Gilmore, 1993;Zurovec et al, 1998;Grumont et al, 1999).…”
mentioning
confidence: 99%